Activities of physically handicapped students in physical education classes in seven public secondary schools in Manila - Nalupta, Fernando Aquilizan 1923- (s.n.], 1964)
The purpose of this study is to identify the activities assigned to the physically handicapped students in physical education classes in seven public secondary schools in Manila. It also aims to analyze whether these activities contribute to the physical and social development of these physically handicapped students. Specifically, the investigator tried to find out the kinds and causes of these physical handicaps.